Hubungan Wayang Kulit Dan Kehidupan Sosial Masyarakat Jawa - Sukirno, Sukirno (Institut Seni Indoensia Surakarta, 2009)
Wayang is a Javanese cultural es-sence inherited hereditary, not just a spectacle and a guide how people should behave in life, but also an order that must dititeni kanti tliti (which is an all natural law that needed to be regularly and judi-ciously adder-ssed) kasunyatan towards and achieve real life. Java for men (men who understand the true) is a way of life puppets, how they behave with others and how aware essence as human beings and how they can relate to the creator. Now a social function for the Javanese wayang has shifted and changed, especially for urban com-munities who consume urban mass culture. Formerly a puppet show and guidance, now they see the puppet confined to enjoy an entertainment. It is very different from an agrarian society tiggal Javanese rural, social function puppets as educational media, ritual, entertainment and information is often held, for example, for this ritual, the village clean, and Ruwatan. Even so if we want to look more deeply, in fact the presence of a puppet in the life of Javanese society is still very strong. In his subconscious, attitude and mindset of Javanese society is still very close to the puppet either visually or philosophy. This can be seen from the emergence of puppet forms that apply to the various fields of life. This paper discusses the above issues, namely the shifting function and the role of puppets in contem-porary Javanese life of the com-munity. Dig up some possible affinity with the Javanese wayang both visually and the philosophy, views of behavior and thought patterns in several aspects of social life, including in the art world recent practice. Keywords: Puppet, Javanese so-ciety, global culture, art.